ENT 530 Social Media Portfolio: Khat By Saloma / Lily Allissa Muhammad Amir - Muhammad Amir, Lily Allissa (2021)
‘Khat by Saloma’ is a personal business where we produced, and sell a modern Islamic contemporary art calligraphy khat frame designs, unlike others. Operated since 2018, ‘Khat by Saloma’ was owned by an experienced designer Norliza Zalaria, or more known as Saloma. Having such experience in designing for almost 28 years, she decides to learn more on arts, so in 2017, she learn calligraphy and gain interest in designing her own khat designs with the Diwani Jali writing style. Notable features of our Unique Selling Proposition (USP) are, we offers an exclusive, high quality khat frames that gives customer no disappointment. ‘Khat by Saloma’ is based on Telok Gadong Kecil, Klang, Selangor, and as well operated online through social media platforms such as Facebook, Instagram, Pinterest and Whatssap. Also not to forget, we also created an official website domain www.artbysaloma.net , for an easy online purchase. We are aware of the competitors in this field, too many of them even sells khat frames with a very cheap price , it might lead ‘Khat by Saloma’ into lots of disadvantages. However, having competitors is a good experience to start up a business. In fact, a healthy rivalry will challenge ‘Khat by Saloma’ to work smarter with the resources that we have.